Princípio da Subsidiariedade, Corporativismo e Educação: para a crítica da gestão participativa - Bezerra, José Eudes Baima (2010)
The overall study aims to examine the introduction of policies to democratic and participatory management in the public education in Brazil, in the limits of the Brazilian State management "reform", with emphasis on the Ceará state experience between 1995 and 2006, considering its articulation within the guidelines issued by the multilateral agencies. In this sense, the study focuses on the ideologies that inform the above process, Corporatism and the Principle of Subsidiarity, examining his reappearance in the political theory underlying the "reform" of the State. It is a documental and bibliographical research based on theoretical and methodological horizon of historical and dialectical materialism. The research resulted in approaches that reveal: management "reform" of the Brazilian State, responsive to the crisis of capital, founded in participatory bases, prefigures a integralist political regime, averse to the political independence of the working class organizations; in the current context, decentralized and participatory management aims to capture, in the State apparatus, the classist representations (corporatism) in the context of governance in which an alleged autonomy in the base is designed to manage the overall strategic plan of the State (principle of subsidiarity); management participatory appears as a sine qua non of accaountability, in other words, the transfer of public services to the sphere of civil society, the sphere of the market; the study of the introduction of participatory management in the Ceará public education web showed the link between the new managerial methods and imperatives posed by the State tax adjustment; the process is not completed, because, in a hand, of the resistance of teachers and students and, in onother, by inaction of governments, or by little attraction exerted on the private sector, although the models of participatory and democratic management continue being the preferred way of introducing of the State managerial "reform".